(Research on The Levels of Awareness and Resposibility of Small Scale Food Industry To Produce A Qualifying and Safe Food) - Sudibyo, Agus; -, Sumarsi (Warta Industri Hasil Pertanian, 2004)
Research on the levels of awareness and responsibility of small scale food industry to produce a qualifying and safe food has been conducted .this research was conducted by carrying out a survey, an interview , plant visit and distribute a questionnaire to the managers/owners of small scale of small scale food industries at six region ,ie jakarta,bogor tangerang,bekasi(jabotabek),bandung (west java) and padang ,bukit tinngi (west sumatera)A random sampling of food products samples that was taken from small scale food industry at traditional market or at the businesses operation was also conducted to identify the food product were safety regulion the results showed that generally ,after the indonesian government decree the food safety regulations,i.e food act no. 7 decree in 1996; lebeling government no. 69 in 1999 on cosumer protection act no. 8 decree in 1999 ; the of food hygiene practices and 36.31% implementation labeling goverment regulation no. 69 decree in 1999.